2021
DOI: 10.1007/s00775-021-01886-4
|View full text |Cite
|
Sign up to set email alerts
|

Protein adsorption/desorption dynamics on Ca-enriched titanium surfaces: biological implications

Abstract: Calcium ions are used in the development of biomaterials for the promotion of coagulation, bone regeneration, and implant osseointegration. Upon implantation, the time-dependent release of calcium ions from titanium implant surfaces modifies the physicochemical characteristics at the implant–tissue interface and thus, the biological responses. The aim of this study is to examine how the dynamics of protein adsorption on these surfaces change over time. Titanium discs with and without Ca were incubated with hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…142 The Ca 2+ -modified implant surface not only enhances osseointegration but also reduces inflammatory responses and promotes vascularization. 43,143 Zhang et al 83 investigated the correlation among Ca 2+ , macrophage polarization, and new bone formation after implanting calcium phosphate-based biomaterials. The results revealed that Ca 2+ activated the Wnt/ β-catenin signaling pathway and then promoted the transcription of arginase-1 (Arg-1) and IL-10 (M2 marker genes) in macrophages.…”
Section: Calcium Ion (Ca 2+ )mentioning
confidence: 99%
“…142 The Ca 2+ -modified implant surface not only enhances osseointegration but also reduces inflammatory responses and promotes vascularization. 43,143 Zhang et al 83 investigated the correlation among Ca 2+ , macrophage polarization, and new bone formation after implanting calcium phosphate-based biomaterials. The results revealed that Ca 2+ activated the Wnt/ β-catenin signaling pathway and then promoted the transcription of arginase-1 (Arg-1) and IL-10 (M2 marker genes) in macrophages.…”
Section: Calcium Ion (Ca 2+ )mentioning
confidence: 99%
“…It is well known that calcium ions are essential for physiological bone metabolism and have the capability to suppress the expression of inflammatory cytokine TNF-α via activating the CaSR signalling cascade and inhibiting NF-κB pathway. 96 Silicon has also been reported to exhibit anti-oxidant and anti-inflammatory effects, which can inhibit the gene expression of TNF-α, COX-2, and iNOS and reduce the generation of NO and IL-6 in macrophages. 97 Recently, Chen et al 98 fabricated barrier collagen membrane coating nanometer-sized Ca 2 ZnSi 2 O 7 , and in vitro and in vivo models indicated that this material strengthened the expression of pro-inflammatory cytokines including TNF-α, IL-1β, IL-6, and IL-18 and activated BMP, canonical Wnt/β-catenin and OSM signaling to induce osteogenic differentiation of BMSCs.…”
Section: Engineering Nanomaterials For Immunomodulation and Bone Rege...mentioning
confidence: 99%
“…The adsorption/desorption patterns of key proteins associated with the coagulation system and the immune response could explain the differences between the in vitro blood clotting and inflammatory potential of the Ti- and Ca-modified implants. 20 Examining the Cu effects on the protein adsorption onto biomaterials should improve our understanding of the role of this element in tissue regeneration and its ability to prevent bacterial infections.…”
Section: Introductionmentioning
confidence: 99%